A PML Method for Electromagnetic Scattering from Two-Dimensional Overfilled Cavities (Communications in Mathematical Research, 2021)
In this paper, we consider electromagnetic scattering problems for two-dimensional overfilled cavities. A half ringy absorbing perfectly matched layer (PML) is introduced to enclose the cavity, and the PML formulations for both TM and TE polarizations are presented. Existence, uniqueness and convergence of the PML solutions are considered. Numerical experiments demonstrate that the PML method is efficient and accurate for solving cavity scattering problems.
Keywords: overfilled cavity; scattering; TM polarization; TE polarization; perfectly matched layer (PML); DtN operator